Training Media Learning for Teachers of MI Citra Taman Siswa - Nur Hidayat (Kontribusia : Research Dissemination for Community Development, 2018)
This community program aims to increase understanding and awareness to educators about the importance of media in the learning process. The subjects of this activity are the teachers of MI Citra Taman Siswa Menganti. In the implementation of this activity, the method used is lecture, question and answer, discussion and practice. The result of the activity shows that with the learning media training activities can improve the understanding and ability of MI Citra Taman Siswa teachers in using media in the learning process. The result of the community program suggests the school to provide supporting training activity with other relevant institution. Finally, the quality of training has to be carefully taken into account to improve teachers’ professionalism.